Urban environment and cognitive and motor function in children from four European birth cohorts - Binter, Anne-Claire; Bernard, Jonathan Y.; Mon-Williams, Mark; Andiarena, Ainara; González-Safont, Llúcia; Vafeiadi, Marina; Lepeule, Johanna; Soler-Blasco, Raquel; Alonso, Lucia; Kampouri, Mariza; Mceachan, Rosie; Santa-Marina, Loreto; et al. (Environment international, 2022)
[Display omitted] •We estimated 13 urban exposures and cognitive and motor function in 5403 children.•Connectivity and land use diversity are negatively associated with verbal abilities.•PM2.5 mediate the positive association of greenness and verbal abilities.•PM2.5 is negatively associated with fine motor function. The urban environment may influence neurodevelopment from conception onwards, but there is no evaluation of the impact of multiple groups of exposures simultaneously. We investigated the association between early-life urban environment and cognitive and motor function in children. We used data from 5403 mother–child pairs from four population-based birth-cohorts (UK, France, Spain, and Greece). We estimated thirteen urban home exposures during pregnancy and childhood, including: built environment, natural spaces, and air pollution. Verbal, non-verbal, gross motor, and fine motor functions were assessed using validated tests at five years old. We ran adjusted multi-exposure models using the Deletion-Substitution-Addition algorithm. Higher greenness exposure within 300 m during pregnancy was associated with higher verbal abilities (1.5 points (95% confidence interval 0.4, 2.7) per 0.20 unit increase in greenness). Higher connectivity density within 100 m and land use diversity during pregnancy were related to lower verbal abilities. Childhood exposure to PM2.5 mediated 74% of the association between greenness during childhood and verbal abilities. Higher exposure to PM2.5 during pregnancy was related to lower fine motor function (-1.2 points (-2.1, -0.4) per 3.2 μg/m3 increase in PM2.5). No associations were found with non-verbal abilities and gross motor function. This study suggests that built environment, greenness, and air pollution may impact child cognitive and motor function at five years old. This study adds evidence that well-designed urban planning may benefit children’s cognitive and motor development.